Intercultural Competence for a Co-existance in a Multicultural Society - Hrvatić, Neven (Array, 2014)
The world of the New Era marked by globalization processes is confronted with an accelerated flow of information, capital, services, products and people. Intercultural interaction due to an increasing interdependence of cultures in the global multicultural society has become daily reality for most people, and cultural encounters imply the necessity of a quality interrelationship based on the idea of interculturalism. The results of empiric research performed on the example of 1, 320 pedagogy students in universities in Croatia, Bosnia and Herzegovina, the Czech Republic and Slovakia have indicated the significant impact of socio-cultural factors at the level of intercultural sensitivity and perception of desired intercultural competences necessary for working in cultural and pluralistic environments.